Odpowiedź :
Odpowiedź:
[tex]A.\ \ -2\frac{1}{3}\cdot(-\frac{3}{7})=\frac{\not7^1}{\not3_{1}}\cdot\frac{\not3^1}{\not7_{1}}=1\\\\\\B.\ \ -\frac{2}{3}\cdot1\frac{1}{2}=-\frac{\not2^1}{\not3_{1}}\cdot\frac{\not3^1}{\not2_{1}}=-1\\\\\\C.\ \ 0,6\cdot(-1\frac{2}{3})=\frac{\not3^1}{\not5_{1}}\cdot(-\frac{\not5^1}{\not3_{1}})=-1\\\\\\D.\ \ -4\frac{2}{3}\cdot3\frac{2}{3}=-\frac{14}{3}\cdot\frac{11}{3}=-\frac{154}{9}=-17\frac{1}{9}\\\\\\E.\ \ -10\cdot0,1=-1[/tex]
Wyrażenia, których wartość jest równa -1 to B , C , E
A) -2 1/3*-3/7=7/3*3/7 i to skróć 3z3 a 7z7 i to wychodzi =1 a z resztą nie wiem